FAKTOR YANG MEMPENGARUHI KEBANGKRUTAN PERBANKAN KONVENSIONAL YANG TERDAFTAR DI BEI DENGAN MODEL ALTMAN Z SCORE - Michelle Corina Angela; Susanto Salim; Syanti Dewi (Jurnal Paradigma Akuntansi, 2026)
The goal of this research is to examine empirically the influence of the variables in the Altman Z-Score, namely Working Capital to Total Assets, Retained Earnings to Total Assets, Earnings Before Interest and Tax (EBIT) to Total Assets, and Market Value Equity to Total Liabilities on Financial Distress in conventional banking listed on the Indonesia Stock Exchange (IDX) in 2019-2021. Samples used in this study were 96 samples selected using the purposive sampling method. Data is processed with Eviews 12. The results of this study indicate that Working Capital to Total Assets, Retained Earnings to Total Assets, Earnings Before Interest and Tax to Total Assets, and Market Value Equity to Total Liabilities have a significant positive effect on financial distress.